ChemInform Abstract: AlCl3 Mediated Unexpected Migration of Sulfonyl Groups: Regioselective Synthesis of 7‐Sulfonyl Indoles of Potential Pharmacological Interest. Issue 6 (20th February 2013) - Prasad, Bagineni; Adepu, Raju; Sandra, Sandhya; Rambabu, D.; Krishna, G. Rama; Reddy, C. Malla; Deora, Girdhar Singh; Misra, Parimal; Pal, Manojit
Abstract The acetylation of indole (IIIe) in the presence of AlCl3 leads to desired 3‐acetyl derivative (VII), whilst the analogous reaction of 2‐tert‐butylindoles (IIIa)—(IIId) is accompanied by an unexpected migration of the sulfonyl group.